Performance Analysis of Intersections along Jalan Abdul Rahman using Sidra Intersection 8.0 - Rosni, Nurul Farah Najwa; Danial, Nur ‘Ain Dalilah; Rosli, Siti Aisyah Anasya; Sanik, Mohd Erwan (Multidisciplinary Applied Research and Innovation, 2023)
Signalized intersection is one of the traffic facilities that is usually provided to link several stretches in an urban road network. From time to time, the signalized phases might need to be revised to maintain reliability during operation due to traffic demand, especially in the developed area. Jalan Abdul Rahman, Muar has been chosen as a study location as it is one of the main entrances to Bandar Maharani Muar. This study was carried out to identify the peak hour and the level of service at the selected intersections. SIDRA Intersections 8.0 software was used to analyze the data to obtain the current performance of intersection due to traffic vehicle flow. The study has found that the peak hour along Jalan Abdul Rahman is from 5.30 p.m. until 6.30 p.m. and the level of service at the intersection of Jalan Abdul Rahman-Lebuh AMJ and Jalan Abdul Rahman-Jalan Sultan Ibrahim/Jalan Parit Haji Baki were verified as the level of service C and F, respectively. These findings could help local authority to monitor the performance of these intersection so intervention can be done to control congestion along Jalan Abdul Rahman.